A prospective multicentre REFCOR study of 470 cases of head and neck Adenoid cystic carcinoma: epidemiology and prognostic factors. (May 2020) - Atallah, Sarah; Casiraghi, Odile; Fakhry, Nicolas; Wassef, Michel; Uro-Coste, Emmanuelle; Espitalier, Florent; Sudaka, Anne; Kaminsky, Marie Christine; Dakpe, Stéphanie; Digue, Laurence; Bouchain, Olivier; Morinière, Sylvain; et al.
Abstract: Background: Adenoid cystic carcinoma (ACC) accounts for 1% of malignant head and neck tumours [1] and 10% of salivary glands malignant tumours. The main objective of our study is to investigate the prognostic factors influencing the event-free survival (EFS) of patients with ACC. Patients and methods: A multicentre prospective study was conducted from 2009 to 2018. All 470 patients with ACC whose survival data appear in the REFCOR database were included in the study. The main judgement criterion was EFS. Both a bivariate survival analysis using log-rank test and a multivariate using Cox model were performed using the R software. Results: Average age was 55 years. Females accounted for 59.4% of the cohort. The body mass index (BMI) was normal in 86% of cases. Tumours were located in minor salivary glands in 60% of cases. T3/T4 stages represented 58%; 89% of patients were cN0. histological grade III was observed on 21% of patients. The EFS and overall 5-year survival rates were 50% and 85%, respectively. After adjustment, the most significant pejorative prognostic factors were age ≥65 years (hazard ratio [HR] = 1.67), BMI<16.5 (HR = 2.62), and lymph node invasion cN (HR = 2.08). Conclusion: Age, BMI and N stage are the three main clinical prognostic factors determining EFS identified in this prospective series of patients with ACC. Such findings open new research perspectives on the influence of these components on initial patient care. Highlights: Head and neck adenoid cystic carcinoma occur more frequently in women (sex ratio: 1.5). Age, body mass index and N stage are the three main clinical prognostic factors influencing event-free survival. Tumour size, perineural invasion and the presence of histological grade III also have a negative influence on prognosis.